UPAYA MENINGKATKAN KEMAMPUAN PROBLEM SOLVING SISWA SD ADHI MEKAR INDONESIA MELALUI PEMBELAJARAN MATEMATIKA BERBASIS EKSPLORASI - Harini, I.; Astawa, I G.S.; Sudatri, N.W.; Adnyana, I G.A.P.; Widiartha, I M. (Buletin Udayana Mengabdi, 2017)
Among all the elementary subjects, mathematics remains a topic that most often appears as the most problematic in the learning process of teaching and learning. The readiness of teachers in teaching mathematics and students are less interested in studying mathematics, are the two key issues to be solved. To make learn math more meaningful for students, the integration of the subjects of mathematics with the real issues are very important. One of the alternative that can be taken to resolve the problem is to design a exploration based math learning. This dedication activities cooperating with SD Adhi Mekar Indonesia as a partner school. The objectives to be achieved through these activities include: (1) the teacher can develop math teaching materials more innovative with exploration based learning (2) see the extent to which the increase in problem solving ability of students through exploration based learning. From the analysis of cross-tabulation between the pre-test and post-test showed that the training on making teaching material based exploration significant effect on the increase in the ability of teachers to make teaching materials based exploration.